The Effect of Competency Development and Work Creativity on Employee Performance - Arifin, Adnan; Mujahid, Mujahid; Suyuthi, Nurmadhani Fitri (Newinera Publisher, 2023)
This study aims to analyze the effect of competency development and work creativity on employee performance at PT Pelindo Makassar. Employee competency and work creativity are seen as two important factors that complement each other in increasing employee productivity and innovation in a dynamic work environment. Competency development ensures that employees have the knowledge and skills needed to carry out tasks efficiently, while creativity allows employees to find innovative solutions to solve problems. This research method uses a quantitative approach with a correlational design to measure the relationship between these variables. Data were collected through structured questionnaires distributed to 164 employees of PT Pelindo Makassar. The sampling technique used was stratified sampling. Data were analyzed using multiple linear regression with the help of SPSS version 25 software. Validity, reliability, normality, multicollinearity, and regression tests were carried out to ensure the quality of the analysis.The results showed that both competency development and work creativity have a significant positive effect on employee performance. Competency development contributes to increased productivity, service quality, and adaptation to change, while work creativity drives innovation, operational efficiency, and job satisfaction. Simultaneously, both variables contribute 58.9% to increased employee performance. These results emphasize the importance of competency and creativity development strategies in improving company performance and competitiveness.